ChemInform Abstract: Yonemitsu‐Type Condensations Catalyzed by Proline and Eu(OTf)3. Issue 15 (April 2015) - Renzetti, Andrea; Boffa, Emanuela; Colazzo, Marco; Gerard, Stephane; Sapi, Janos; Chan, Tak‐Hang; Nakazawa, Hiroshi; Villani, Claudio; Fontana, Antonella
Abstract: The products are obtained as single diastereomers or as mixtures of diastereomers.